'Publish or perish': implications for novice African university scholars in the neoliberal era. Issue 2 (3rd April 2022) - Vurayai, Simon; Ndofirepi, Amasa Philip
ABSTRACT: This theoretical paper uses content analysis by drawing from the literature on the implications of the varied conceptions of 'Publish or perish' maxim to novice African academics in the neoliberal context. Neoliberal politics has defined education and research in particular as a commodity to be bought and sold as controlled by the profit motive and related market forces. As a result, novice African academics have been marginalised in the production and dissemination of knowledge on a global scale due to weapons such as cultural imperialism, linguicide, epistemicide and poor funding. We recommend that African academics should be independent of the private economic and political interests and serve the public interest in promoting their language, culture, and knowledge through their journals.